RUANG BANACH PADA RUANG BARISAN 1  , p  DAN  - Wahidah Alwi (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2014)
The main object of the vectors are the vectors can be addedtogether and generate a vector, and produces a number is multipliedby another vector. Any set of objects with properties like this arecalled